Proteasomal degradation of BRAHMA promotes Boron tolerance in Arabidopsis - Sakamoto, Takuya (Nat Commun, 2018)
High levels of boron (B) induce DNA double-strand breaks (DSBs) in eukaryotes, including plants. Here we show a molecular pathway of high B-induced DSBs by characterizing Arabidopsis thaliana hypersensitive to excess boron mutants. Molecular analysis of the mutants revealed that degradation of a SWItch/Sucrose Non-Fermentable subunit, BRAHMA (BRM), by a 26S proteasome (26SP) with specific subunits is a key process for ameliorating high-B-induced DSBs. We also found that high-B treatment induces histone hyperacetylation, which increases susceptibility to DSBs. BRM binds to acetylated histone residues and opens chromatin. Accordingly, we propose that the 26SP limits chromatin opening by BRM in conjunction with histone hyperacetylation to maintain chromatin stability and avoid DSB formation under high-B conditions. Interestingly, a positive correlation between the extent of histone acetylation and DSB formation is evident in human cultured cells, suggesting that the mechanism of DSB induction is also valid in animals.